Significance of Cardiac Troponins as an Identification Tool in COVID-19 Patients Using Biosensors: An Update - Rasmi, Yousef; Mosa, Osama F.; Alipour, Shahriar; Heidari, Nadia; Javanmard, Farzaneh; Golchin, Ali; Gholizadeh-Ghaleh Aziz, Shiva (Frontiers in Molecular Biosciences, 2022)
Coronavirus Disease 2019 (COVID-19) has rapidly developed as a global health emergency. Respiratory diseases are major causes of morbidity and mortality in these patients with a spectrum of different diseases, from asymptomatic subclinical infection to progression of severe pneumonia and subsequent acute respiratory distress syndrome. Individuals with cardiovascular disease are more likely to become infected with SARS-CoV-2 and develop its severe symptoms. Hence, the mortality rate of patients with underlying cardiovascular disease is over three times. Furthermore, noting that patients with a history of cardiovascular disease are more likely to have higher cardiac biomarkers, especially cardiac Troponins, in the infected patients, especially those with severe disease, making these patients more susceptible to cardiac damage through SARS-2-CoV. Biomarkers are important in decision-making to facilitate the efficient allocation of resources. Viral replication in the heart muscle can lead to a cascade of inflammatory processes that lead to fibrosis and ultimately cardiac necrosis. Elevated Troponin may indicate damage to the heart muscle and may predict death. After the first Chinese analysis, increased cardiac Troponin value was observed in a significant proportion of patients, suggesting that myocardial damage is a possible pathogenic mechanism leading to severe disease and death. However, the prognostic performance of Troponin and whether its value is affected by different comorbidities present in COVID-19 patients are not known. This review aimed to assess the diagnostic value of Troponin to offer insight into pathophysiological mechanisms and reported new assessment methods, including new biosensors for Troponin in patients with COVID-19.